Peran Penting Satpol PP dalam Menegakkan Ketertiban Umum Kota Surabaya - Melyka Ayu Ananda; Wiwik Handayani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The aim of this research is to study the role of Satpol PP in maintaining public order in the city of Surabaya. Satpol PP is responsible for complying with Regional Regulations and maintaining public order in accordance with the Law. This research uses a qualitative approach and a descriptive approach. This study found that the role of the Surabaya City Satpol PP is in controlling street vendors, controlling unlicensed buildings, and controlling advertising. City Regional Regulation Number 2 of 2020 concerning Implementation of Public Order and Community Peace regulates this action.